Ifosfamide‐induced acute kidney injury in a patient with leiomyosarcoma: A case report - Javad Boskabadi; Ehsan Yousefi‐Mazhin; Ebrahim Salehifar (Cancer Reports, 2022)
Abstract Background Leiomyosarcoma (LMS) is an aggressive soft tissue sarcoma that is derived from smooth muscles. Ifosfamide is in use for advanced metastatic LMS. Case A‐44‐years old woman with a chief complaint of pain in the epigastric area, itching, coughing, nausea, and vomiting was referred to the emergency department. Her medical history was LMS. She had taken Ifosfamide and mesna in her last chemotherapy. Seventy percent of her liver and her left kidney were removed 4 years ago to prevent the progress of the disease. Because of the increase in the level of creatinine and urea in the initial laboratory report, a Shaldon catheter was inserted for the patient, and she was under emergency dialysis for 3 h. In addition, during the six‐day hospitalization period, dialysis was done two times. Finally, the patient was discharged with improved clinical tests accompanied by a twice‐weekly dialysis order. Conclusion Ifosfamide is metabolized into chloroacetaldehyde, which can cause acute kidney injury. Recovery from acute kidney injury may not always be perfect and can lead to some degree of chronic kidney disease. Opposite to hemorrhagic cystitis, mesna is not effective in preventing ifosfamide's nephrotoxicity and N‐acetylcysteine may be effective in the prevention of this nephrotoxicity.